Bio-Based Hydrogels With Ion Exchange Properties Applied to Remove Cu(II), Cr(VI), and As(V) Ions From Water - Sánchez, Julio; Dax, Daniel; Tapiero, Yesid; Xu, Chunlin; Willför, Stefan (Frontiers in Bioengineering and Biotechnology, 2021)
Hydrogels with ion exchange properties were synthesized from compounds derived from wood biopolymer hemicellulose and from commercial vinyl monomers to be tested as active materials for the removal of Cu(II), Cr(VI), and As(V) ions. The hemicellulose O-acetyl galactoglucomannan (GGM) was used as the precursor material, and through a transesterification reaction, GGM was converted into a macromonomer O-acetyl galactoglucomannan-glycidyl methacrylate (GGM-GMA). Subsequently, the GGM-GMA macromonomer, containing more than one methacrylate group, was used as a cross-linking agent in the synthesis of hydrogels through free radical polymerization reactions in combination with a 2-acrylamido-2-methyl-1-propanesulfonic acid monomer to produce a cation exchange hydrogel. Also, (3-acrylamidopropyl) trimethylammonium chloride monomer was applied together with the GGM-GMA to form hydrogels that can be used as anion exchange material. The hydrogels were characterized by Fourier transform-infrared FT-IR, 1H-NMR spectroscopy, and thermogravimetric analysis (TGA), as well as derivative thermogravimetry (DTG). The microstructure of the hydrogels was characterized by scanning electron microscopy (SEM) analysis with X-ray microanalysis EDS. The results obtained regarding the absorption capacity of the Cu(II), Cr(VI), and As(V) ions were studied as a function of the pH value and the initial concentration of the metal ions in the solutions. Absorption was carried out in consecutive batches, and it was found that the poly(GGM-GMA/AMPSH) hydrogel reached an absorption capacity of 90 mg g-1 for Cu(II). The poly(GGM-GMA/APTACl) hydrogel reached values of 69 mg g-1 and 60 mg g-1 for Cr(VI) and As(V) oxyanions, respectively. Tests with polymer blends (mixtures of anionic and cationic hydrogels) were also carried out to remove Cu(II), Cr(VI) and As(V) ions from multi-ionic solutions, obtaining satisfactory results.